Metabolic engineering of Zymomonas mobilis for co-production of D-lactic acid and ethanol using waste feedstocks of molasses and corncob residue hydrolysate - Hu, Mimi; Bao, Weiwei; Peng, Qiqun; Hu, Wei; Yang, Xinyu; Xiang, Yan; Yan, Xiongying; Li, Mian; Xu, Ping; He, Qiaoning; Yang, Shihui (Frontiers in Bioengineering and Biotechnology, 2023)
Lactate is the precursor for polylactide. In this study, a lactate producer of Z. mobilis was constructed by replacing ZMO0038 with LmldhA gene driven by a strong promoter PadhB, replacing ZMO1650 with native pdc gene driven by Ptet, and replacing native pdc with another copy of LmldhA driven by PadhB to divert carbon from ethanol to D-lactate. The resultant strain ZML-pdc-ldh produced 13.8 ± 0.2 g/L lactate and 16.9 ± 0.3 g/L ethanol using 48 g/L glucose. Lactate production of ZML-pdc-ldh was further investigated after fermentation optimization in pH-controlled fermenters. ZML-pdc-ldh produced 24.2 ± 0.6 g/L lactate and 12.9 ± 0.8 g/L ethanol as well as 36.2 ± 1.0 g/L lactate and 40.3 ± 0.3 g/L ethanol, resulting in total carbon conversion rate of 98.3 ± 2.5% and 96.2 ± 0.1% with final product productivity of 1.9 ± 0.0 g/L/h and 2.2 ± 0.0 g/L/h in RMG5 and RMG12, respectively. Moreover, ZML-pdc-ldh produced 32.9 ± 0.1 g/L D-lactate and 27.7 ± 0.2 g/L ethanol as well as 42.8 ± 0.0 g/L D-lactate and 53.1 ± 0.7 g/L ethanol with 97.1 ± 0.0% and 99.1 ± 0.8% carbon conversion rate using 20% molasses or corncob residue hydrolysate, respectively. Our study thus demonstrated that it is effective for lactate production by fermentation condition optimization and metabolic engineering to strengthen heterologous ldh expression while reducing the native ethanol production pathway. The capability of recombinant lactate-producer of Z. mobilis for efficient waste feedstocks conversion makes it a promising biorefinery platform for carbon-neutral biochemical production.